An Integrated Review of Emoticons in Computer-Mediated Communication - Aldunate, Nerea; González-Ibáñez, Roberto (Frontiers in Psychology, 2017)
Facial expressions constitute a rich source of non-verbal cues in face-to-face communication. They provide interlocutors with resources to express and interpret verbal messages, which may affect their cognitive and emotional processing. Contrarily, computer-mediated communication (CMC), particularly text-based communication, is limited to the use of symbols to convey a message, where facial expressions cannot be transmitted naturally. In this scenario, people use emoticons as paralinguistic cues to convey emotional meaning. Research has shown that emoticons contribute to a greater social presence as a result of the enrichment of text-based communication channels. Additionally, emoticons constitute a valuable resource for language comprehension by providing expressivity to text messages. The latter findings have been supported by studies in neuroscience showing that particular brain regions involved in emotional processing are also activated when people are exposed to emoticons. To reach an integrated understanding of the influence of emoticons in human communication on both socio-cognitive and neural levels, we review the literature on emoticons in three different areas. First, we present relevant literature on emoticons in CMC. Second, we study the influence of emoticons in language comprehension. Finally, we show the incipient research in neuroscience on this topic. This mini review reveals that, while there are plenty of studies on the influence of emoticons in communication from a social psychology perspective, little is known about the neurocognitive basis of the effects of emoticons on communication dynamics.